India’s Foreign Economic Policy in The Current Global Impact (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study examines the evolution and current dynamics of India’s foreign economic policy within the context of global economic transformations. It traces the historical shift from a protectionist economy to a liberalized and globally integrated framework and highlights the impact of economic reforms on trade, investment, and global economic governance. The findings indicate that India has successfully diversified its trade relations, liberalized foreign direct investment (FDI) regimes, and increased its participation in multilateral economic forums such as the G20 and WTO. Moreover, India has utilized economic diplomacy to promote digital innovation, sustainable energy, and climate-resilient infrastructure. While significant achievements are evident, the study also identifies ongoing challenges related to regulatory hurdles, global trade uncertainties, and geopolitical risks. The analysis concludes that India’s foreign economic policy is at a pivotal juncture, with opportunities to further strengthen its role as a key player in shaping future global economic policies.